2021
DOI: 10.1108/ijm-05-2020-0252
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting unethical pro-organizational behavior: harnessing the effects of responsible leadership and leader–member exchange

Abstract: PurposeLeadership styles appear to influence unethical pro-organizational behavior (UPB), but there has been little empirical research on employees' ethical behavior as an outcome of responsible leadership. This study examines the positive effect of responsible leadership on unethical pro-organizational behavior (UPB) via the mediator, leader–member exchange (LMX).Design/methodology/approachResponses from 200 full-time working employees in Pakistan were collected in two waves, and structural equation modeling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…Therefore, researchers have paid increasing attention to determining how to suppress the occurrence of UPB. Existing studies have showed that organizational punishment [25], responsible leadership [26], and organizational climate [27] can prevent and suppress UPB. The confirmation of the negative moderating role of ethical climate rules adds weight to organizational attempts to prevent and suppress UPB.…”
Section: The Moderated Mediation Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, researchers have paid increasing attention to determining how to suppress the occurrence of UPB. Existing studies have showed that organizational punishment [25], responsible leadership [26], and organizational climate [27] can prevent and suppress UPB. The confirmation of the negative moderating role of ethical climate rules adds weight to organizational attempts to prevent and suppress UPB.…”
Section: The Moderated Mediation Testmentioning
confidence: 99%
“…Therefore, the purpose of research focused on the antecedents of UPB is not to promote UPB, but rather to inhibit UPB and promote the sustainable development of the organization. Although some studies show that organizational punishment [25], responsible leadership [26], and organizational climate can effectively reduce the occurrence of UPB [27], UPB research is still in its infancy, and more inhibitory factors need to be discovered to help organizations suppress and prevent UPB. Some studies show that an organizational ethical climate can have an inhibitory effect on employees' unethical behavior [28].…”
Section: Introductionmentioning
confidence: 99%
“…The other is to identify the inhibitors (e.g., moral identity; Matherne et al, 2018 ), thus advising managers to strengthen those inhibitors. In the latter research stream, given that leaders usually have great influences on employees, more and more scholars have shifted their attention to the leader-related inhibitors ( Cheng et al, 2019 ; Cheng and Lin, 2020 ; Inam et al, 2021 ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Extant research has mainly used social learning theory to explain the direct effect of responsible leadership on unethical pro-organizational behavior ( Cheng et al, 2019 ; Inam et al, 2021 ). Bandura (1977) noted that his social learning theory had drawn much nourishment from the academic thought regarding information processing.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it is important because of protection, acquisition, connection, and understanding ( Lawrence and Pirson, 2015 ). Several studies have recently been published in the leadership literature to explain and comprehend the practice of RL and to investigate its impact on employee outcomes in various sectors ( Inam et al, 2021 ; Javed et al, 2021 ; Zhang et al, 2021 ), but very scant in the education sector.…”
Section: Introductionmentioning
confidence: 99%